Post-crisis Monetary Policy Implementation : Insights from the Bank of Korea’s Responses to Crises - Kontio, Miro (My University, 2025)
Globalization has created opportunities for innovative and export-driven companies by opening access to new markets, but increased interdependence has also heightened the risk of local crises escalating into global complications. Financial liberalization offers greater access to capital for firms and banks, yet the easing of capital controls leaves economies vulnerable to rapid capital movements. This thesis combines a theoretical framework, South Korea’s experiences, and key empirical findings to explore how central banks should implement monetary policies following crises. An examination of South Korea’s rapid economic growth, its culmination in the Asian Financial Crisis, and the Bank of Korea’s diverse crisis responses provides insights into the necessity of timely liquidity provision and robust financial supervision. The findings underline the importance of maintaining substantial foreign currency reserves—regardless of the exchange rate regime—to stabilize the currency while recognizing the difficulty of preventing currency and maturity mismatches in an open economy. This thesis recommends that central banks should implement predictable monetary policy through instruments such as forward guidance and inflation targeting to strengthen investor trust, while expansionary measures are crucial for alleviating liquidity squeezes and combating slow growth and elevated market rates induced by crises.

Globalisaatio on luonut mahdollisuuksia innovatiivisille ja vientivetoisille yrityksille avaamalla pääsyn uusille markkinoille, mutta tämä lisääntynyt keskinäisriippuvuus on kasvattanut paikallisten kriisien riskiä eskaloitua kansainvälisiksi ongelmiksi. Rahoitusmarkkinoiden vapautuminen tarjoaa yrityksille ja pankeille paremman pääsyn pääomaan, mutta pääomakontrollien lievittäminen tekee talouksista alttiimpia nopeille pääomaliikkeille. Tämä tutkielma yhdistää teoreettisen viitekehyksen, Etelä-Korean kokemukset ja keskeiset empiiriset havainnot tutkiakseen, kuinka keskuspankkien tulisi toteuttaa rahapolitiikkaa kriisien jälkeen. Tarkastelu Etelä-Korean nopeasta talouskasvusta, sen huipentumisesta Aasian talouskriisiin ja Korean keskuspankin moninaisista kriisihallintatoimista tarjoaa näkemyksiä oikea-aikaisen likviditeetin tarjoamisen ja vankan finanssivalvonnan tarpeellisuudesta. Havainnot alleviivaavat merkittävien valuuttavarantojen ylläpitämisen tärkeyttä—riippumatta valuuttakurssijärjestelmästä—valuutan vakauttamiseksi, tunnistaen samalla, että valuutta- ja maturiteettiriskien ehkäisy avoimessa taloudessa on haastavaa. Tämä tutkielma suosittelee, että keskuspankkien tulisi toteuttaa ennakoivaa rahapolitiikkaa välineiden, kuten ennakoivan johdatuksen ja inflaatiotavoitteen, avulla vahvistaakseen sijoittajien luottamusta, kun taas elvyttävät toimenpiteet ovat keskeisiä likviditeettipulien lievittämisessä sekä kriisien aiheuttaman hitaan kasvun ja korkeiden markkinakorkojen torjumisessa.
Keywords: monetary policy; South Korea; crisis management; liquidity; capital movements; fi=Taloustiede|en=Economics|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|